Identifying and quantifying cultural factors that matter to the IT workforce: An approach based on automated content analysis - Schmiedel, Theresa; Müller, Oliver; Debortoli, Stefan; vom Brocke, Jan (European Conference on Information Systems)
Organizational culture represents a key success factor in highly competitive environments, such as, the IT sector. Thus, IT companies need to understand what makes up a culture that fosters employee performance. While existing research typically uses self-report questionnaires to study the relation of culture and the success of companies, the validity of this approach is often discussed and researchers call for new ways of studying culture. Therefore, our research goal is to present an alternative ap-proach to culture analysis for examining which cultural factors matter to the IT workforce. Our study builds on 112,610 online reviews of Fortune 500 IT companies collected from Glassdoor, an online platform on which current and former employees can anonymously review companies and their man-agement. We perform an automated content analysis to identify cultural factors that employees em-phasize in their reviews. Through a regression analysis on numerical employee satisfaction ratings, we find that a culture of learning and performance orientation contributes to employee motivation, while a culture of assertiveness and gender inegalitarianism has a strong negative influence on em-ployees’ satisfaction in the IT workforce. Future research can apply our approach as an alternative method to quantifying culture and its impact on other variables.

Du genre de la littérature. Introduction - Schlieper, Hendrik; Steinbrügge, Lieselotte (lendemains 162, 163)

Zur sprachlichen Bildung aus der Perspektive der Pädagogischen Psychologie - Buhl, Heike M.; Wiescholek, Sabrina (Handbuch Sprache in der Bildung)
Der Beitrag stellt pädagogisch-psychologische Perspektiven auf sprachliche Bildung dar. Um zu einem Verständnis der Disziplin zu gelangen, werden methodische Zugänge der Psychologie als empirischer Wissenschaft sowie ihr Blick auf Bildung, Sprache und sprachliche Bildung dargestellt. Es kristallisiert sich heraus, dass der Begriff der Bildung in der Pädagogischen Psychologie selten verwendet wird, seine Inhalte aber in Form von Kompetenz, z. B. Lesekompetenz, wie auch von Literacy Gegenstand der Pädagogischen Psychologie sind. Zwei Teilaspekte der Thematik werden vertieft: Zum einen wird sprachliche Bildung als Wissenserwerb anhand von Texten betrachtet. Herangezogen wird dabei ein kognitionspsychologischer Zugang zum Textverstehen, ergänzend werden die Lesemotivation wie auch Lesestrategien berücksichtigt. Zum anderen wird aus einer sozialisationstheoretischen Perspektive betrachtet, wie Kinder den Zugang zu Sprache finden. Wir fokussieren dabei v. a. auf den Kontext der Familie und betrachten Family-Literacy-Programme. In allen Teilbereichen werden Konzepte der Beschreibung und Erklärung um Interventionsansätze ergänzt.

Equivariant bifurcations in four-dimensional fixed point spaces - Lauterbach, Reiner; Schwenker, Sören (Dynamical Systems)
In this paper we continue the study of group representations which are counterexamples to the Ize conjecture. As in previous papers we find new infinite series of finite groups leading to such counterexamples. These new series are quite different from the previous ones, for example the group orders do not form an arithmetic progression. However, as before we find Lie groups which contain all these groups. This additional structure was observed, but not used in the previous studies of this problem. Here we also investigate the related bifurcations. To a large extent, these are closely related to the presence of mentioned compact Lie group containing the finite groups. This might give a tool to study the bifurcations related to all low dimensional counterexamples of the Ize conjecture. It also gives an indication of where we can expect to find examples where the bifurcation behaviour is different from what we have seen in the known examples.
Keywords: Computer Science Applications; General Mathematics

Die Entwicklung der Systemorientierung der Textsorte 'Schulprogramm' anhand ihrer Titelblätter – Eine systemtheoretisch-textsortenlinguistische Untersuchung - Markewitz, Friedrich (Textsortenwandel vom 9. bis zum 19. Jahrhundert)

Spectral analysis of the diffusion operator with random jumps from the boundary - Kolb, Martin; Krejčiřík, David (Mathematische Zeitschrift)
Using an operator-theoretic framework in a Hilbert-space setting, we perform a detailed spectral analysis of the one-dimensional Laplacian in a bounded interval, subject to specific non-self-adjoint connected boundary conditions modelling a random jump from the boundary to a point inside the interval. In accordance with previous works, we find that all the eigenvalues are real. As the new results, we derive and analyse the adjoint operator, determine the geometric and algebraic multiplicities of the eigenvalues, write down formulae for the eigenfunctions together with the generalised eigenfunctions and study their basis properties. It turns out that the latter heavily depend on whether the distance of the interior point to the centre of the interval divided by the length of the interval is rational or irrational. Finally, we find a closed formula for the metric operator that provides a similarity transform of the problem to a self-adjoint operator.

Ethik kleiner Dinge. Adalbert Stifter, Francis Ponge, W.G. Sebald - Öhlschläger, Claudia (Weimarer Beiträge. Zeitschrift für Literaturwissenschaft, Ästhetik und Kulturwissenschaften 3, 62. Jg.)

Roland Barthes´ Tagebuch der Trauer als kleine Form - Öhlschläger, Claudia (xComparatio. Zeitschrift für Vergleichende Literaturwissenschaft., Heft 2)

Transience and recurrence of a Brownian path with limited local time - Kolb, Martin; Savov, Mladen (The Annals of Probability)
In this note we investigate the behaviour of Brownian motion conditioned on a growth constraint of its local time which has been previously investigated by Berestycki and Benjamini. For a class of non-decreasing positive functions f(t);t>0, we consider the Wiener measure under the condition that the Brownian local time is dominated by the function f up to time T. In the case where f(t)/t3/2 is integrable we describe the limiting process as T goes to infinity. Moreover, we prove two conjectures in [BB10] in the case for a class of functions f, for which f(t)/t3/2 just fails to be integrable. Our methodology is more general as it relies on the study of the asymptotic of the probability of subordinators to stay above a given curve. Immediately or with adaptations one can study questions like the Brownian motioned conditioned on a growth constraint of its local time at the maximum or more generally a Levy process conditioned on a growth constraint of its local time at the maximum or at zero. We discuss briefly the former.

Whey protein with potassium bicarbonate supplement attenuates the reduction in muscle oxidative capacity during 19 days of bed rest - Bosutti, Alessandra; Salanova, Michele; Blottner, Dieter; Bühlmeier, Judith; Mulder, Edwin; Rittweger, Jörn; Yap, Moi Hoon; Ganse, Bergita; Degens, Hans (Journal of Applied Physiology)
The effectiveness of whey protein plus potassium bicarbonate-enriched diet (WP+KHCO 3 ) in mitigating disuse-induced changes in muscle fiber oxidative capacity and capillarization was investigated in a 21-day crossover design bed rest study. Ten healthy men (31 ± 6 yr) once received WP+KHCO 3 and once received a standardized isocaloric diet. Muscle biopsies were taken 2 days before and during the 19th day of bed rest (BR) from the soleus (SOL) and vastus lateralis (VL) muscle. Whole-body aerobic power (V̇o 2 max ), muscle fatigue, and isometric strength of knee extensor and plantar flexor muscles were monitored. Muscle fiber types and capillaries were identified by immunohistochemistry. Fiber oxidative capacity was determined as the optical density (OD) at 660 nm of succinate dehydrogenase (SDH)-stained sections. The product of fiber cross-sectional area and SDH-OD (integrated SDH) indicated the maximal oxygen consumption of that fiber. The maximal oxygen consumption supported by a capillary was calculated as the integrated SDH in its supply area. BR reduced isometric strength of knee extensor muscles ( P < 0.05), and the fiber oxidative capacity ( P < 0.001) and V̇o 2 max ( P = 0.042), but had no significant impact on muscle capillarization or fatigue resistance of thigh muscles. The maximal oxygen consumption supported by a capillary was reduced by 24% in SOL and 16% in VL ( P < 0.001). WP+KHCO 3 attenuated the disuse-induced reduction in fiber oxidative capacity in both muscles ( P < 0.01). In conclusion, following 19 days of bed rest, the decrement in fiber oxidative capacity is proportionally larger than the loss of capillaries. WP+KHCO 3 appears to attenuate disuse-induced reductions in fiber oxidative capacity.
Keywords: Physiology (medical); Physiology

Zum Verhältnis von ästhetischer Bildung und postmigrantischem Theater. Nurkan Erpulats Verrücktes Blut als Herausforderung für die Bildungsinstitution - Kißling, Magdalena (Institutionalisierte Pädagogik in Literatur und Film. Vom Mittelalter bis zur Gegenwart)

Zwischen Öffnung und neuerlicher Schließung - Steigerwald, Jörn (Um 1700 Die Formierung der europäischen Aufklärung)

Anthologie und Analyse - Steigerwald, Jörn (Aufklärung und Imagination in Frankreich (1675-1810))

Kausalattributionen von Leseerfolgen und Lesemisserfolgen bei Kindern im Leseunterricht der Grundschule - Knickenberg, Margarita; Hellmich, Frank (Facetten grundschulpädagogischer und -didaktischer Forschung)

Grammatische Fähigkeiten deutschsprachiger Kinder zwischen vier und neun Jahren mit Fokus auf dem Kasuserwerb - Ulrich, Tanja (Language and inclusion as an opportunity?! Expertise and innovation for day-care centers, schools and practices)

Wo haben sich die Bauernhoftiere versteckt? Eine Unterrichtsstunde zur Förderung der Dativmarkierung im sprachheilpädagogischen Unterricht - Ulrich, Tanja; Mayer, A (Sprachförderung und Sprachtherapie in Schule und Praxis)

Sprachtherapeutische Diagnostik mit dem Mottier-Test. Viele Normierungen und viele Fragezeichen - Ulrich, Tanja (Forum Logopädie)

Der Dativerwerb -Forschungsergebnisse und ihre therapeutischen Konsequenzen - Ulrich, Tanja; Knickenberg, Margarita; Penke, M; Lüdtke, U; Motsch, H.J (Logos)

Gattung und Subjekt in Roland Barthes' "Fragments d’un discours amoureux“ - Süwolto, Leonie (Comparatio, 8.2)

Altern in einer alterslosen Gesellschaft. Literarische und filmische Imaginationen - Süwolto, Leonie